THU0429 Clinical significance of increased serum levels of FGF23 in fibrous dysplasia. (15th June 2017) - Florez, H; Mandelikova, S; Filella, X; Monegal, A; Guañabens, N; Peris, P
Abstract : Background: Fibrous dysplasia of bone (FD) is an uncommon skeletal disorder, caused by missense mutations of the GNAS1 gene and is characterized by the development of fibro-osseous lesions that replace normal bone. FD can present with a broad spectrum of clinical manifestations, including the development of hypophosphatemic osteomalacia which is due to the production of the phosphaturic hormone fibroblast growth factor 23 (FGF-23) by the dysplastic bone tissue. Nevertheless, the prevalence of this clinical complication is not well known. Objectives: To analyse the serum levels of FGF-23 in patients with FD and determine their relationship with the extension and activity of the disease, as well as with serum phosphate levels. Methods: Twelve patients (7F:5M) with FD with a mean age of 50.67±16.4 years (24–79) were included. The clinical reports of the patients were reviewed, with special attention to the extension and activity of the disease, number and location of the affected bones, clinical complications and treatments received. Serum FGF-23 values were recorded in all subjects (determined by Immunotopics, CA, USA [measuring FGF23 C- terminal], normal value <130 RU/ml), as well as serum phosphate and calcium values, bone turnover markers and their evolution with treatment. Results: Serum levels of FGF-23 were increased (>130 RU/ml) in 6/12 patients (50%). In patients with and without high FGF-23 levels the number of affected bones (2.2±2 vs . 1.9±1, respectively) and the skeletal locations of FD were similar as was the age in both groups of patients (48.2±14 vs . 53.2±19 years). In addition, FD disease activity and extension were similar in the two groups as were the bone turnover marker values (FAO, PINP and CTx). Strikingly, differences between serum phosphate values were not observed between the two groups (FGF23 >130: 3.9±0.9 mg/dl vs . FGF23 <130: 3.5±0.6 mg/dl). Indeed, none of the patients with high FGF-23 levels had low serum phosphate values. Following bisphosphonate (zoledronate) treatment, there were no significant changes in FGF-23 values. Nevertheless, an increase of 123% was found in one patient receiving denosumab, although hypophosphatemia was not associated. Conclusions: Patients with FD frequently present elevated FGF-23 values with no effects on serum phosphate levels, thereby suggesting the presence of an alteration in processing this protein in the dysplastic bone tissue in this disease. The role of denosumab treatment in FD and its repercussion on FGF-23 levels need further study. Disclosure of Interest: None declared